2017
DOI: 10.3347/kjp.2017.55.4.457
|View full text |Cite
|
Sign up to set email alerts
|

Historical Details about the Meat Consumption and Taeniases in Joseon Period of Korea

Abstract: Previous paleoparasitological studies of Joseon specimens established that the prevalence of Taenia infection was not much different from that of the early 20th century Korean population. As many of taeniases originally diagnosed as Taenia saginata in South Korea were revealed to be actually Taenia asiatica, which share a common intermediate host with T. solium (the pig), Joseon people must have ingested raw pork frequently. However, the current examination of extant Joseon documents revealed that the populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…infection in the Joseon mummies was calculated as 6.7% (2/30). This rate is quite comparable with the 1920’s Korean reports of human taeniases (6–16%) [ 142 ]. However, the prevalence became remarkably lower based on fecal examinations of the general population in Korea, 0.7–1.9% in the 1970s, 0.3–1.1% in the 1980s, 0.02–0.06% in the 1990s, and 0.00–0.04% in 2004–2012 [ 138 ].…”
Section: Estimation Of the Prevalence Of Helminthic Infections Among ...supporting
confidence: 87%
See 1 more Smart Citation
“…infection in the Joseon mummies was calculated as 6.7% (2/30). This rate is quite comparable with the 1920’s Korean reports of human taeniases (6–16%) [ 142 ]. However, the prevalence became remarkably lower based on fecal examinations of the general population in Korea, 0.7–1.9% in the 1970s, 0.3–1.1% in the 1980s, 0.02–0.06% in the 1990s, and 0.00–0.04% in 2004–2012 [ 138 ].…”
Section: Estimation Of the Prevalence Of Helminthic Infections Among ...supporting
confidence: 87%
“…However, the prevalence became remarkably lower based on fecal examinations of the general population in Korea, 0.7–1.9% in the 1970s, 0.3–1.1% in the 1980s, 0.02–0.06% in the 1990s, and 0.00–0.04% in 2004–2012 [ 138 ]. It has been suggested that the Joseon people may have been infected with T. saginata more frequently than T. asiatica , since the consumption of beef was quite common among the Joseon people, and pork was not consumed as much as we thought [ 142 ].…”
Section: Estimation Of the Prevalence Of Helminthic Infections Among ...mentioning
confidence: 97%
“…During the Joseon period, people raised cattle and horses mainly as beasts of burden (i.e., for farming or transportation purposes) and only secondarily as sources of meat. Accordingly, the Joseon government, for the purposes of securing a stable labor force for its agrarian society, strictly prohibited what it considered to be the premature slaughter of animals (Shin et al 2017). Consistent with this line of thought, historians have argued that Joseon society cattle were slaughtered only when, due to age or other infirmity, they could no longer be put to farming or transportation uses (Kim 2018).…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), over 3 billion people around the world suffer from one or more parasitic diseases, which are widespread and a leading cause of morbidity and mortality in populations [ 1 ]. Parasites have infected humans for thousands of years, and nearly all known human-specific parasites have been found in ancient feces [ 2 , 3 ]. Indeed, no organism is protected against parasites.…”
Section: Introductionmentioning
confidence: 99%